PENGARUH PENGGUNAAN SERBUK CANGKANG LANGKITANG ( FAUNUS ATER ) SEBAGAI BAHAN TAMBAH TERHADAP KUAT TEKAN BETON NORMAL - A, Arman; Wardi, Syafri; Sonata, Herix; Iqbal, Muhammad (Ensiklopedia of Journal, 2024)
Langkitang shell is a food waste that has potential benefits that can be used as powder as a mixture in the manufacture of pozzolanic containing CaCO3 (Calcium Carbonate), SiO2 (Silicon Dioxide) which these compounds are also found in sand and cement. The purpose of this research is to know the physical properties of sand and the physical properties of langkitang shell powder as a constituent of normal concrete, to know the effect of using langkitang shell powder as an added ingredient to the concrete mix on the compressive strength of normal concrete, and to know the optimum percentage of langkitang shell as an added material for get the maximum normal compressive strength of concrete. The research method used is the experimental method, the experimental method in this study was carried out by comparing the concrete to be tested. In this study, the percentage of the variation of langkitang powder used was 1%, 2.5%%, and 4%. With the test object in the form of a cube with dimensions of 15 cm x 15 cm x 15 cm, and the planned compressive strength of K-250. The results obtained from normal concrete with a compressive strength of 269.46 kg/cm², and the results of the quality of concrete used K-250 which were tested at the age of 28 days were 12 samples and consisted of 3 variations, each variation of 3 samples (1 %, 2.5%,4% ). From the research, it was obtained that the compressive strength of the mixed concrete variation of 1% was 323.4 kg/cm², 2.5% was 321.6 kg/cm², and the results of the 4% concrete compressive strength was 254.63 kg/cm². Researchers can conclude based on the results from the laboratory of PT. Jaya Sentrikon Indonesia. The results of the compressive strength of concrete decreased in the 4% variation mixture, namely 254.63 kg/cm², and the highest concrete compressive strength at 1% was 323.4 kg/cm². It can be concluded in this study that the more substances mixed with langkitang shell powder are used, the lower the value of the compressive strength of the resulting concrete.Keywords: Langkitang Shell, Sikacim Concrete Additive, Compressive Strength, Normal Concrete.